A long noncoding RNA CHAIR protects the heart from pathological stress. Issue 13 (17th July 2020) - Qian, Yanxia; Zhang, Mingming; Zhou, Ningtian; Xu, Xiaohan; Zhang, Jiahui; Ding, Qiang; Wang, Junhong
Abstract: Mammalian genomes have been found to be extensively transcribed. In addition to classic protein coding genes, a large numbers of long noncoding genes (lncRNAs) have been identified, while their functions, especially in heart diseases, remain to be established. We hypothesized that heart failure progression is controlled by tissue-specific lncRNAs. In the present study, we found that the cardiac-enriched lncRNA 4632428C04Rik, named as cardiomyocyte hypertrophic associated inhibitory RNA ( CHAIR ), is dynamically regulated during heart development, is expressed at low levels in embryonic hearts and accumulated at high levels in adult hearts. More interestingly, the lncRNA was down-regulated during cardiac hypertrophy and failure both in mice and humans. Importantly, loss of lncRNA CHAIR has no effects on normal hearts, whereas it results in accelerated heart function decline, increased hypertrophy, and exacerbated heart failure in response to stress. In contrast, restoring the expression of lncRNA CHAIR rescued the hearts from hypertrophy and failure. DNMT3A was recruited to CHAIR promoter during heart failure to suppress its expression. Reciprocally, CHAIR interacted with DNMT3A to inhibit its DNA-binding activity. Taken together, our data revealed a new cardioprotective lncRNA that represses heart failure through an epigenetic mechanism.